Training on how to use Social Media Wisely and Ethically - Herman Herman; Imam Riadi; Dikky Praseptian M; Faiz Isnan Abdurrachman; Syahrani Lonang (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Nowadays, the behavior of users in social media arguably represent human behavior in the real world. Training on how to use social media wisely and ethically to young ages is needed to grow the good behavior. Based on a preliminary study, the ages of students in SMK Kesehatan Binatama is considered a terget of such training. 15 years old dominates with 63.6% followed by 16 years old with 29.3% according to age which has the highest penetration rate of social media users reaching 99.16%, namely ages 13-18 years. The activeness of students in social media reaches 99%. The number of hours students use social media where 10.1 % stated between 0-2 hours, 40.4% stated 2-5 hours, 36.4% stated 5-10 hours and 11.1 % more than 10 hours. Knowledge training on social media has been carried out several times but must continue to be carried out along with the development of social media technology and the shift in the age of its users. Training activities with wise and ethical materials using social media have been successfully held with the expected results. Participants' knowledge and insight, namely students can increase with information regarding what can and should not be done when using social media, information about hoaxes and cyberbullying and the ITE Law can be understood properly. The survey results also show an increase in the knowledge provided from the criteria of understanding to criteria of very understanding with an increase from the average score on the pre-test 2.96 with a percentage of 59.2% to the average score on the post-test 3.64 with a percentage of 72.8%.